Crohn's and Colitis Canada's 2021 Impact of COVID-19 and Inflammatory Bowel Disease in Canada: Children and Expectant Mothers With Inflammatory Bowel Disease. (5th November 2021) - Benchimol, Eric I; Carroll, Matthew W; Geist, Rose; Griffiths, Anne M; Huang, James Guoxian; Mack, David R; Bernstein, Charles N; Bitton, Alain; Jones, Jennifer L; Kaplan, Gilaad G; Kuenzig, M Ellen; Lee, Kate; et al.
Abstract: Coronavirus disease 2019 (COVID-19) in children with inflammatory bowel disease (IBD) typically results in a mild infection, similar to those without IBD. Children and adolescents have less severe manifestations of COVID-19 compared to older people, whether or not they have IBD. However, some IBD medications (in particular, corticosteroids) are associated with more severe COVID-19. During the first year of the global pandemic, more IBD care was provided with online technology, necessitated by efforts to reduce hospital and clinic visits. Additionally, non-endoscopic monitoring of inflammation has been required due to the cancellation of non-urgent procedures, resulting in longer endoscopy wait-times. In contrast, pregnant people (with and without IBD) who contract COVID-19 are at increased risk of severe manifestations, death and preterm delivery, making them a priority for severe acute respiratory syndrome coronavirus 2 protective measures and vaccination. Few studies have examined effect of COVID-19 on IBD-related disease activity in pregnant people with IBD. The pandemic has significantly affected the mental health and sense of well-being of children and their families, as well as pregnant people with IBD. These groups were much more likely to experience anxiety and depression compared with prior to the pandemic, even while concern has mostly abated regarding the effect of IBD medications and COVID-19 severity. Unfortunately, the availability of mental health care providers who specialize in people with IBD has not kept pace with the increasing demand.